1995
DOI: 10.1037/0882-7974.10.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Unique and interactive effects of depression, age, socioeconomic advantage, and gender on cognitive performance of normal healthy older people.

Abstract: A sample of 4,243 residents of Manchester, England and Newcastle-upon-Tyne, England, aged 50 to 93 years, completed the Beck Depression Scale (A.T. Beck, C.H. Ward, M. Mendelson, J. Mock, & J. Erbaugh, 1961) and a battery of 6 different cognitive tests. Beck scores were low, indicating gradations of dysphoria rather than clinical depression. Beck scores did not vary with age but were significantly higher for women than for men and for disadvantaged than for advantaged socioeconomic groups. Measures of fluid, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
82
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 21 publications
(39 reference statements)
13
82
2
1
Order By: Relevance
“…However, as Blazer & Williams (1980) point out, clinically significant depression represents only the upper end of a continuum of states of unhappiness found in randomly selected older samples of older people. Further, even within ranges well below levels of clinical concern, scores on the Beck Depression Inventory (Beck et al 1961) correlate negatively with performance on laboratory tests of fluid intelligence and memory (Rabbitt et al 1995). This raises the question of why mental abilities are impaired by even mild discontent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as Blazer & Williams (1980) point out, clinically significant depression represents only the upper end of a continuum of states of unhappiness found in randomly selected older samples of older people. Further, even within ranges well below levels of clinical concern, scores on the Beck Depression Inventory (Beck et al 1961) correlate negatively with performance on laboratory tests of fluid intelligence and memory (Rabbitt et al 1995). This raises the question of why mental abilities are impaired by even mild discontent.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier analyses had found that both depression and cognitive performance vary with levels of socioeconomic advantage (Rabbitt et al 1995). This was taken into consideration by grouping participants by reference to the UK Office of Population Censuses and Surveys classification of occupational categories (1980).…”
Section: Participants Demographics and Beck Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…The WAIS~R vocabulary scores of younger and older subjects did not differ significantly in either ofthe experiments (both ts < I). These scores were collected as part of the longitudinal study (see Rabbitt, Donlan, Bent, McInnes, & Abson, 1993).…”
Section: General Information On Subjectsmentioning
confidence: 99%
“…As suggested by Bassuk, Berkman, and Wypij (1998), individuals with depression may exhibit decreased cognitive performance due to motivational and attentiveness problems. An increase in the vulnerability of cognitive processes (Rabbitt, Donlan, Watson, McInnes, & Bent, 1995) to sleep quality might be the consequence (Vance, Roberson, McGuinness, & Fazeli, 2010).…”
Section: Introductionmentioning
confidence: 99%